Mapping the photocatalytic activity and ecotoxicology of Au, Pt/TiO2 composite photocatalysts - Hampel Boglárka (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2018)
In the present research gold and platinum nanoparticles were deposited simultaneously on three different commercial titania photocatalysts (Evonik Aeroxide P25, Aldrich rutile, and Aldrich anatase). For the synthesis of the composites two noble metal reduction methods (in situ and impregnation) and three noble metal deposition routes (i.e., by changing their deposition order, Au/Pt, Pt/Au, and Au-Pt simultaneously) were used. The photocatalytic performances of the nanocomposites were evaluated under UV irradiation, through degradation of oxalic acid and photocatalytic hydrogen production. The best performing photocatalyst was obtained by sequential noble metal deposition (first Au followed by Pt) on Evonik Aeroxide P25. The morphological and structural properties were studied/investigated by using DRS, TEM, HRTEM, EDX, and XRD. The gold and platinum nanoparticles formed clusters in most of the cases. Furthermore, the ecotoxicity of the composites was investigated using Lemna minor growth inhibition tests using static "lake" approach completed by DLS and ROS indirect measurements. The toxic effect of the composites which showed the highest photocatalytic activity did not differ from that of their commercial counterparts, showing that these nanoparticles were eco-friendly. This result shows the great capacity of these materials to be used in the next future in photocatalytic applications.